Estudo taxonômico dos "lagartos" fósseis (Lepidosauria: Squamata) da Bacia de São José de Itaboraí (Paleoceno), estado do Rio de Janeiro - Carvalho, Alberto Barbosa de (2001)
ln this dissertation 84 selected "lizard" specimens of the Paleocene deposits from the São José de Itaboraí Basin were studied. The material consists of isolated, sometimes incomplete, premaxillae, maxillae and dentaries. Seven taxa were recognized as follows: Iguania incertae sedis (new gen. and esp.), Gekkonidae (new gen. and esp.), Scincomorpha incertae sedis (two taxa – new genus and species), Teiidae (new gen. and esp.), and Anguimorpha incertae sedis (two taxa – new genus and species). The presence of these taxa shows important paleobiogeographic implications. Among those is the occurrence of a member of Iguania, that were previously reported in the Cretaceous of South America, corroborating with the hypothesis that this clade was diversified in the New World from the south. The occurrence of Gekkonidae extends the fossil record of this clade in the New World to the Paleocene, reinforcing the idea that early members of this clade might have arrived to this continent from Africa by rafting sometime during the Late Cretaceous (as some other group of vertebrates hypothetically did), when a large seaway was already placed between those continents, and in latter times dispersed to the North. The presence of a xantusiid-like in the Paleocene deposits of the São José de Itaboraí < Basin, that possibly represents the sister group to the Xantusiidae, suggests that this clade might have originated in South America and than dispersed to Central and North America during the Cenozoic Era. The fossil "lizard" diversity of the Paleocene deposits of the São José de Itaboraí Basin, in complemented by the presence of two new taxa referable to the Anguimorpha, which is the first occurrence of this group in South America. They might represent new anguimorphan taxa that are closely related either to Anguiodea or Platynota.